Relação nitrogênio não proteico e proteína verdadeira em suplementos na recria de bezerros Nelore - Fernandes, Rodolfo Maciel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective of this study was to evaluate the effect of elevated protein intake and also different rates of protein degradation, coupled with the use of energy on performance, fermentation parameters, forage intake and supplement in Nellore, recreated in Brachiaria brizantha. Marandu during the dry season transition waters. The treatments were: energy protein supplement with 25% CP (C-25), energy protein supplement with 40% CP, 1/3 of the PB of vegetable and two thirds of urea (40-2/3 NNP) energy protein supplement with 40% CP, 1/3 of the PB urea and 2/3 of vegetable origin (40-1/3NNP), energy protein supplement with 40% CP, 1/2 PB of urea and 1/2 of vegetable origin (40-1/2 NNP). The pasture assessments and weights of animals were taken every 28 days. Each period also estimates individual and collective consumption of supplement and forage plus fermentation parameters were performed. The experimental design was a complete randomized to evaluate the performance blocks, experimental areas and the blocking factor paddock as the experimental unit. Evaluations of ruminal fermentation and the consumption design was a Latin square (4X4). There were no treatment effects on ruminal pH, acetate, propionate and isobutyrate, however, the animals fed supplement with high levels of protein and higher degradation rate (40-2/3NNP), have higher ruminal concentrations of butyrate and isovalerate. There was interaction between treatments and periods of assessment on animal performance. The animals supplemented with higher levels of protein combined with lower rates of protein degradation (40-1/3 NNP) exhibit superior performance when compared to animals consuming lower levels of protein (C- 25) or high levels of protein with high degradation rates (40-2/3 NNP) at the beginning of the transition dry waters . We conclude that elevated levels of protein combined with lower rates of degradation is an alternative ...

Objetivou-se com o presente estudo avaliar o efeito da elevação do aporte proteico e também diferentes taxas de degradação proteica, aliados a utilização de energia, sobre o desempenho, parâmetros fermentativos, consumo de forragem e de suplemento em animais Nelore, recriados em pastagem de Brachiaria brizantha cv. Marandu durante a estação de transição seca-águas. Os suplementos foram: Suplemento proteico energético com 25% de PB (C-25), suplemento proteico energético com 40% de PB, sendo 1/3 da PB de origem vegetal e 2/3 de uréia (40-2/3NNP), suplemento proteico energético com 40% de PB, sendo 1/3 da PB de uréia e 2/3 de origem vegetal (40-1/3NNP), suplemento proteico energético com 40% de PB, sendo 1/2 da PB de uréia e 1/2 de origem vegetal (40-1/2NNP). As avaliações de pasto e as pesagens dos animais foram realizadas a cada 28 dias. A cada período também foram realizadas estimativas de consumo coletivo de suplemento além de parâmetros ruminais. O delineamento experimental foi o de blocos completos aos acaso para a avaliação de desempenho, sendo as áreas experimentais o fator de blocagem e o piquete como unidade experimental. Para as avaliações de parâmetros ruminais e consumo o delineamento adotado foi em quadrado latino (4X4). Não houve efeito dos suplementos sobre o pH ruminal, concentração de acetato, propionato e isobutirato, porém, os animais que consumiram suplemento com altos níveis de proteína e maiores taxa de degradação (40-2/3NNP), apresentaram maiores concentrações ruminais de butirato e isovalerato. Observou-se interação entre suplementos e períodos de avaliação sobre o desempenho animal. Os animais suplementados com maiores níveis de proteína aliados as menores taxas de degradação proteica (40-1/3NNP) apresentam desempenho superiores quando comparadas aos animais consumindo menores níveis de proteína (C-25) ou níveis elevados ...
Keywords: Bovinos de corte; Bezerro; Nelore (Zebu); Proteínas; Suplementos dieteticos; Proteins